Parasite induced changes in contact behaviour is affected by parasitic status of group members - Alex M. M. Morris; Giles T. Innocent; Emma J. A. Cunningham; Darren P. Croft; Spiridoula Athanasiadou; Michael R. Hutchings; Lesley A. Smith (Behavioral Ecology and Sociobiology, 2025)
Understanding how parasitism may affect social behavior and social networks is key to understanding the impact of infection on a population. Infection can disrupt social networks by altering the behavior of both infected individuals (e.g. by reducing activity) and the behavior of uninfected individuals (e.g. avoiding sick individuals), both of which can have an impact on social group dynamics and parasite transmission. Here we test experimentally how parasitism affects social contact behavior and social network structure using a common parasite infection of sheep. Three treatment groups, each with 4 replicate social groups were established (i) Parasitised; all lambs were infected with a parasitic nematode, (ii) Non-parasitised; all lambs remained uninfected (iii) Mixed; part of each group were infected, and part of the group remained uninfected. Contact behaviours of each individual were recorded using proximity loggers during four phases of infection (pre-parasite, pre-patent, patent-parasite, post-parasite). We found infected individuals in the parasitised and mixed groups reduced contact frequency following infection. Despite the reduction in contacts between infected animals in the mixed group, non-infected individual’s maintained pre-parasite levels of social interactions with their infected conspecifics. These results demonstrate how infection can impact the social behavior of all animals within a group, and how the expression of behavioral change may depend on the parasitic status of all group members and the response of uninfected conspecifics. Significance statement Parasitism is known to influence animal behavior and social interactions; however groups of animals will often contain individuals of different parasitic status. Understanding the behavioral response of both infected and uninfected members of a group is important to predict the consequences of infection throughout a population. We show, under experimental conditions, that parasitism not only reduces the frequency of contacts between infected lambs at the earliest stages of infection in both mixed and single-parasitic state groups, but also the degree of behavior change exhibited by infected animals is influenced by the parasitic status of other individuals within the group. We also show that although infected animals in mixed-state groups had reduced contact frequency with their infected groupmates, non-infected animal’s maintained pre-infection levels of social interactions.